Modern and contemporary: reflections on the concepts of individual time and death - Augusto, Maria Helena Oliva (Tempo Social, 1994)
The relations that bind members of a society together and allow them to formulate shared ideas about the world, such as the ways in which the nature of time is perceived, also permit them to attribute specific meanings to the various dimensions of their existence. This paper deals with the meaning of death for members of contemporary society and with the related issue of the meaning of life. To accomplish this. I will discuss certain aspects of modern social life, as conceived of in the late 18th and early 19th centuries. Principally, I will deal with the emergence of the individual, the idea of freedom and changes in the notion of time- features which will then be identified in the contemporary world. Changes in the meaning of life and death as perceived in people´s contemporary experience will hopefully become clear by comparing these two moments.